Host Defense Versus Immunosuppression: Unisexual Infection With Male or Female Schistosoma mansoni Differentially Impacts the Immune Response Against Invading Cercariae - Sombetzki, Martina; Koslowski, Nicole; Rabes, Anne; Seneberg, Sonja; Winkelmann, Franziska; Fritzsche, Carlos; Loebermann, Micha; Reisinger, Emil C. (Frontiers in Immunology, 2018)
Infection with the intravascular diecious trematode Schistosoma spp. remains a serious tropical disease and public health problem in the developing world, affecting over 258 million people worldwide. During chronic Schistosoma mansoni infection, complex immune responses to tissue-entrapped parasite eggs provoke granulomatous inflammation which leads to serious damage of the liver and intestine. The suppression of protective host immune mechanisms by helminths promotes parasite survival and benefits the host by reducing tissue damage. However, immune-suppressive cytokines may reduce vaccine-induced immune responses. By combining a single-sex infection system with a murine air pouch model, we were able to demonstrate that male and female schistosomes play opposing roles in modulating the host’s immune response. Female schistosomes suppress early innate immune responses to invading cercariae in the skin and upregulate anergy-associated genes. In contrast, male schistosomes trigger strong innate immune reactions which lead to a reduction in worm and egg burden in the liver. Our data suggest that the female worm is a neglected player in the dampening of the host’s immune defense system and is therefore a promising target for new immune modulatory therapies.